2012
DOI: 10.2527/jas.2011-4837
|View full text |Cite
|
Sign up to set email alerts
|

Selection for ovulation rate in rabbits: Direct and correlated responses estimated with a cryopreserved control population1

Abstract: a cryopreserved control population Selection for ovulation rate in rabbits: Direct and correlated responses estimated with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…In the rabbit selection experiment for ovulation rate cited earlier, the estimated difference between selected and control lines for prenatal survival from ovulation to birth was the same, -0.12 (HPD 95% =-0.20, -0.04; Laborda et al, 2012b). The results confirmed that a moderate increased of ovulation rate by hormonal treatment could be used to assess the timing of prenatal mortality in ovulation rate selection experiments.…”
Section: Survival Ratessupporting
confidence: 66%
See 2 more Smart Citations
“…In the rabbit selection experiment for ovulation rate cited earlier, the estimated difference between selected and control lines for prenatal survival from ovulation to birth was the same, -0.12 (HPD 95% =-0.20, -0.04; Laborda et al, 2012b). The results confirmed that a moderate increased of ovulation rate by hormonal treatment could be used to assess the timing of prenatal mortality in ovulation rate selection experiments.…”
Section: Survival Ratessupporting
confidence: 66%
“…Low concentration of eCG was used to increase ovulation rate to a level similar to that obtained after ten generations of selection for ovulation rate (Laborda et al, 2012b). In this selection experiment, an increase of 2.1 ova [highest posterior density region of the difference at 95% (HPD95%)=1.3, 2.9] was estimated but no correlated response in litter size was found due to a decrease in prenatal survival (-0.12 kits).…”
Section: Ovulation Rate Number Of Implanted Embryos and Foetusesmentioning
confidence: 95%
See 1 more Smart Citation
“…Cryopreservation of mammalian embryos has benefitted both breeding and biomedical research in recent decades, due in part to the improvement of techniques related to vitrification, freezing-thawing processes, and transfer procedures. To this end, rabbit embryo banking has allowed the preservation and spread of genetically superior animals over different countries [34] and the possibility of evaluating the genetic gain in maternal lines [4][5][6][7] without cumulative genetic drift variance [35]. Nevertheless, it is known that these techniques induce changes in environ-mental and maternal side effects modifying the embryo gene expression and methylation pattern [19,20,36], the transcriptomic and proteomic placental profile [21], and their viability [29,37], but little is known regarding the long-term effects on the derived progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Strain rederivation from cryopreserved embryos has been used to assess the genetic improvement of quantitative traits such as prenatal survival, litter size, and growth characteristics in polytocous species such as mice, rats, and rabbits [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%